2015
DOI: 10.1124/jpet.114.217653
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Anti–Claudin-1 Antibodies as Candidate Therapeutics against Hepatitis C Virus

Abstract: Claudin-1 (CLDN1), a known host factor for hepatitis C virus (HCV) entry and cell-to-cell transmission, is a target molecule for inhibiting HCV infection. We previously developed four clones of mouse anti-CLDN1 monoclonal antibody (mAb) that prevented HCV infection in vitro. Two of these mAbs showed the highest antiviral activity. Here, we optimized the anti-CLDN1 mAbs as candidates for therapeutics by protein engineering. Although Fab fragments of the mAbs prevented in vitro HCV infection, their inhibitory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
(52 reference statements)
2
19
0
Order By: Relevance
“…The ability of anti-CLDN-1 human mAbs to inhibit infection by different HCV isolates was not unexpected and was in line with previous observations made with rat and mouse anti-CLDN-1 antibodies (Fofana et al, 2010;Fukasawa et al, 2015;Mailly et al, 2015;Yamashita et al, 2015). Most importantly, mAbs B9X and D10X displayed binding affinity for cell-displayed CLDN-1 and IC 50 values comparable with the rat anti-CLDN-1 mAb OM-7D3, which was recently shown to prevent HCV infection and to clear persistent infection in a human liver-chimeric mouse model without detectable toxicity .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The ability of anti-CLDN-1 human mAbs to inhibit infection by different HCV isolates was not unexpected and was in line with previous observations made with rat and mouse anti-CLDN-1 antibodies (Fofana et al, 2010;Fukasawa et al, 2015;Mailly et al, 2015;Yamashita et al, 2015). Most importantly, mAbs B9X and D10X displayed binding affinity for cell-displayed CLDN-1 and IC 50 values comparable with the rat anti-CLDN-1 mAb OM-7D3, which was recently shown to prevent HCV infection and to clear persistent infection in a human liver-chimeric mouse model without detectable toxicity .…”
Section: Discussionsupporting
confidence: 75%
“…In particular, we previously showed that the human anti-SRB1 mAb C-1671 completely prevents infection and intrahepatic spread of multiple HCV genotypes in vivo in human liver-chimeric mice (Meuleman et al, 2012). Human mAbs against CLDN-1 and OCLN have not been reported yet, but rat, mouse and mouse/human chimeric anti-CLDN-1 antibodies were found to efficiently inhibit infection by HCV of major genotypes in cell culture (Fofana et al, 2010;Yamashita et al, 2015) and some of them eliminate chronic HCV infection without detectable toxicity when administered to human liver-chimeric mice Mailly et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As such, claudins are attractive antiviral targets. Indeed, antibodies and peptides targeting CLDN1 have been shown to be highly effective against HCV [27, 30, 54, 60, 73, 85, 100]. These antibodies are thought to block formation of the nonphysiological CLDN1-CD81 co-receptor complex during HCV entry, and thus lack any obvious toxic effects for the host.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies that target CLDN1 interfere with the formation of the co-receptor complex [54]. These antibodies pan-genotypically inhibit cell-free infection and cell-to-cell transmission of HCV in human hepatoma cells [27, 54, 100]. Strikingly, anti-CLDN1 antibodies prevent HCV infection of human liver chimeric mice [30, 60] and were even able to cure chronically HCV-infected liver chimeric mice [60] without any detectable toxicity.…”
Section: Claudins and Viral Entrymentioning
confidence: 99%
“…Human-mouse chimeric antibodies were prepared as described previously [12]. Briefly, cDNA encoding the heavy-chain and light-chain variable domains of 3A2 (anti-CLDN-1) were grafted onto the pFUSE-CHIg-hG1 and pFUSE2-CLIg-hk vectors (InVivoGen, San Diego, CA), respectively.…”
Section: Preparation Of Human-mouse Igg1 Chimeric Anti-cldn-1 Monoclomentioning
confidence: 99%